Efficacy comparison of rosuvastatin vs simvastatin on blood lipid and microinflammatory state in the maintenance hemodialysis patients - XU Fang; NIE Da-qing; CHEN Wen-li; LI Li (Linchuang shenzangbing zazhi)
Objective To compared the efficacy of rosuvastatin vs simvastatin on blood lipid and microinflammatory state in maintenance hemodialysis( MHD) patients. Methods Seventy-eight MHD patients were enrolled between Feb. 2015 to Mar. 2016,and divided into two groups: rosuvastatin group and simvastatin group. Rosuvastatin group was treated with high flux hemodialysis therapy and rosuvastatin( 10 mg,once every for 6 months). Simvastatin group was given high flux hemodialysis therapy and simvastatin( 20 mg,once every day for 6 months). The general information,microinflammatory index and serum lipids were compared between two groups. Results There was no significant difference between two groups in terms of age,time of hemodialysis,BMI,Hb,MQSGA score and primary diseases. As compared with before therapy,hs-CRP,TNF-α,IL-6,TC,TG and LDL-C were significantly decreased in rosuvastatin groupafter treatment for 6 months. The levels of hs-CRP,IL-6 and TNF-( in rosuvastatin group were significantly lower than those in simvastatin group after treatment for 6 months [( 2. 25 ± 1. 21) vs( 3. 34 ± 2. 02),P =0. 004;( 7. 28 ± 3. 68) vs( 10. 17 ± 3. 69),P < 0. 001;( 2. 14 ± 0. 86) vs( 5. 24 ± 1. 18),P < 0. 001,respectively]. The level of HDL-C was significantly increased in these two groups after treatment for 6 months as compared with that before treatment. However,there was no significant difference between these two groups in terms of HDL-C after treatment for 6 months. Conclusions Rosuvastatin is better than simvastatin in the treatment of MHD patients.